Calculation of Thermal Conductivity of Low‐Porous, Isotropic Plutonic Rocks of the Crust at Ambient Conditions From Modal Mineralogy and Porosity: A Viable Alternative for Direct Measurement?. Issue 10 (29th October 2018) - Fuchs, S.; Förster, H. ‐J.; Braune, K.; Förster, A.
Abstract: Thermal conductivity (λ) is an essential physical property of minerals and rocks and fundamental in constraining the thermal field of the lithosphere. In case that adequate samples to measure λ are not available, it could be indirectly inferred from calculation. One of the most widely applied indirect methods for rocks involve modal mineralogy and porosity as parameters that are incorporated into mathematical mean or mixing models. Robust inferences from these approaches for crystalline rocks were impeded by a small number of studied samples or restriction to certain rock types. We employ this method and examine its applicability to low‐porosity plutonic rocks by calculating bulk thermal conductivity λb for 45 samples covering the entire range from gabbro/diorite to granite. We show that the use of the harmonic‐mean model for both rock matrix and porosity provided a good match between λb.meas and λb.calc of <10% deviation (2σ), with relative and absolute errors amounting to 1.4 ± 9.7% and 4.4 ± 4.9%, respectively. The results of our study constitute a big step forward to a robust conclusion on the overall applicability of the harmonic‐mean model for inferring λb of isotropic, low‐porosity, mafic to silicic plutonic and metamorphic rocks with an acceptable magnitude of error. Drill cuttings and enclaves form particularly interesting objects for application of this method, as they are poorly suited for direct λ measurement. Well‐derived λ values for those rocks would permit to calculate heat flow and to model more profoundly the thermal state of the deeper lithosphere. Key Points: Modal mineralogy permits matrix thermal conductivity (λ) calculation with 2σ‐uncertainty of <15% using the harmonic‐mean model Uncertainty is reduced to <10% if rock porosity is implemented in the calculation procedure Method is particularly valuable for inferring λ of drill cuttings and enclaves, promoting heat‐flow calculation and geotherm computation